Promotion of psychotherapeutic services on Instagram and their Ethical in Chile - Klener Hernández, Hans; Miranda Olivares, Cristóbal; Barrera Miranda, Thiare; Espinoza Soto, Adriana (Revista Española de Comunicación en Salud, 2026)
Introduction: Mental health has become a central issue in Chile, within a context of high demand and unequal access to care. In this scenario, Instagram has gained a relevant role in promoting psychotherapeutic services, generating new forms of communication between professionals and potential users. Objectives: This qualitative study analyzes the meanings that psychotherapists attribute to this type of advertising and the associated ethical challenges. Method: An online focus group was conducted with eight recently graduated professionals, complemented by photo-elicitation using psychotherapy advertisements from Instagram. An inductive content analysis was applied. Results: Three main dimensions were identified: psychotherapy as a consumer good, marked by tensions between price and quality; the mediatization of practice, associated with the emergence of the “therapist influencer”; and proposals to address ethical challenges. Conclusion: These practices reflect tensions between market logics and ethics, implying communicative risks, but also opening opportunities to strengthen transparent training in mental health delivered through social media.